Making Foreign Aid Effective Nepal’s Success Stories Underscorethe Criticality of Empowerment at the Grassroots - Shrestha, Bihari Krishna (NCWA Annual Journal, 2023)
The rationale supporting foreign aid has been that it enhances the investment capabilities of poor countries to achieve accelerated national development. But Nepal's experiences suggest that there is more to it than that. Foreign aid can be effectively delivered only if sufficient institutional preconditions are put in place in the country.